Third mandibular molar coronectomy: a way to prevent iatrogenic inferior alveolar nerve injuries-an systematic review - Lenfant Benoît; Haese Kevin; Kimakhe Said; Lesclous Philipe (EDP Sciences, 2018)
Introduction: In the field of oral and maxillo-facial surgery, the avulsion of third mandibular molar is a very common procedure. However, and although the injury on the alveolar inferior nerve is very rare, the neurological risk must not be underestimated. Indeed, it may lower the patient's quality of life in a significant way. The coronectomy is a technique that allows us to avoid this risk. It consists in remaining in place the third mandibular molar's roots. Educational objectives: After a clinical introduction to this surgical technique, the main characteristics of this type of procedure will be presented with the help of an exhaustive literature review. Thus, we will refer to the following subjects: the obvious decrease of neurological risks, the potential pre and post-operating complications, the potential necessity of an endodontic treatment for the residual roots, the becoming of these same roots, and finally the bony and mucosal cicatrization of the operated area. Conclusion: Every oral surgeon should have in mind this technique of coronectomy and master it. Indeed, when the case justifies it, the benefits are numerous for the patient.